2015
DOI: 10.1111/1744-7917.12207
|View full text |Cite
|
Sign up to set email alerts
|

Use of electroporation as an option to transform the horn fly, Haematobia irritans: a species recalcitrant to microinjection

Abstract: The horn fly, Haematobia irritans, is a serious pest of cattle in North America. The control of horn flies has primarily relied on insecticides. However, the heavy use of insecticides has led to the development of insecticide resistance in horn flies. Novel methods to control horn flies are greatly needed. Transgenic technology is an effective tool to genetically modify insects and may lead to novel methods of pest control based on genomic approaches. Here we report a piggyBac-mediated transformation of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Babesiosis and anaplasmosis are prevalent wherever R. microplus and R. annulatus occur in Mexico (62)(63)(64)(65)(66) , and 75 % of the national cattle herd is considered to be at risk of becoming infected with B. bovis and B. bigemina (67) . However; we were unable to estimate the economic impact of babesiosis and anaplamosis on the cattle industry in Mexico because key epidemiological data, such as description of specific enzootic instability regions, mortality and incidence of babesiosis and anaplasmosis outbreaks, and number of abortions due to clinical cases and seasonal occurrence of outbreaks were not found during the search of the scientific literature.…”
Section: Potential Impact Of Cattle Ticksmentioning
confidence: 99%
See 1 more Smart Citation
“…Babesiosis and anaplasmosis are prevalent wherever R. microplus and R. annulatus occur in Mexico (62)(63)(64)(65)(66) , and 75 % of the national cattle herd is considered to be at risk of becoming infected with B. bovis and B. bigemina (67) . However; we were unable to estimate the economic impact of babesiosis and anaplamosis on the cattle industry in Mexico because key epidemiological data, such as description of specific enzootic instability regions, mortality and incidence of babesiosis and anaplasmosis outbreaks, and number of abortions due to clinical cases and seasonal occurrence of outbreaks were not found during the search of the scientific literature.…”
Section: Potential Impact Of Cattle Ticksmentioning
confidence: 99%
“…The horn fly, Haematobia irritans, is one of the most economically important pests of cattle worldwide (12,65) . It is an obligate hematophagous ectoparasite that feeds almost exclusively on cattle.…”
Section: Potential Impact Of Haematobia Irritansmentioning
confidence: 99%
“…The 3xP3 promoter has been successfully used as an adult eye and ocelli marker for transgenesis in Drosophila , houseflies, beetles, butterflies, mosquitoes, as well as flatworms ( González-Estévez et al, 2003; Hediger et al, 2001; Horn et al, 2000; Kokoza et al, 2001; Lorenzen et al, 2003; Marcus et al, 2004 ). Although the artificial 3xP3 promoter is widely used; it is not universal and is non-functional in organisms such as the tephritid fly ( Schetelig and Handler, 2013a ) and has potentially weaker functionality in horn flies ( Xu et al, 2016 ). Similarly, our previous work showed that 3xP3 is non-functional in ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Similar difficulties were experienced when attempting to use microinjection for gene transfection in closely related H. i. irritans eggs. In this instance, the researchers opted to use electroporation, which is unsuitable for the introduction of bacteria [58].…”
Section: Discussionmentioning
confidence: 99%